Fungal Mushrooms: A Natural Compound With Therapeutic Applications - Chugh, Rishi Man; Mittal, Pooja; MP, Namratha; Arora, Tanu; Bhattacharya, Tanima; Chopra, Hitesh; Cavalu, Simona; Gautam, Rupesh K. (Frontiers in Pharmacology, 2022)
Fungi are extremely diverse in terms of morphology, ecology, metabolism, and phylogeny. Approximately, 130 medicinal activities like antitumor, immunomodulation, antioxidant, radical scavenging, cardioprotective and antiviral actions are assumed to be produced by the various varieties of medicinal mushrooms. The polysaccharides, present in mushrooms like β-glucans, micronutrients, antioxidants like glycoproteins, triterpenoids, flavonoids, and ergosterols can help establish natural resistance against infections and toxins. The interest in mycotherapy needs the commitment from the scientific and clinical community so that the clinical trials can be performed and these therapeutic agents can be proven to be safe and therapeutically effective. Clinical trials have been performed on mushrooms like Agaricus blazei Murrill Kyowa for their anticancer effect, A. blazei Murrill for its antihypertensive and cardioprotective effects, and some other mushrooms had also been evaluated for their neurological effects. The safety and therapeutic effectiveness of the fungal mushrooms had shifted the interest of biotechnologists toward fungal nanobiotechnology as the drug delivery system due to the vast advantages of nanotechnology systems. In complement to the vital nutritional significance of medicinal mushrooms, numerous species have been identified as sources of bioactive chemicals. Moreover, there are unanswered queries regarding its safety, efficacy, critical issues that affect the future mushroom medicine development, that could jeopardize its usage in the twenty-first century